ContructioOf the Meaning Of "Environment" For Children "Si Bolang" Broadcast on Trans7: (Studies In Betung Village And Tanjung Kukuh Village Okut District) - Dion Hanggara; Yenrizal Yenrizal; Badaruddin Azarkasyi (TABAYYUN, 2023)
This research is entitled "Korean Girlband Fanboy Communication Behavior (Study on PF Entertainment Dance Cover Community in Palembang)" which aims to determine the communication behavior of K-pop girl band fanboys and the effects that occur after liking the K-pop girl band. This type of research uses qualitative methods. Collection techniques the data in this study were collected using interviews, observation, and documentation. The primary data source of this study was interviews with members of the PF Entertainment dance cover community in Palembang. Secondary data sources from this study consisted of books, journals, previous theses, and websites related to this research. This study uses Social Learning Theory, which explains that human behavior can be formed from observing and then the behavior is studied. This research results in a change in communication behavior towards K-pop girl band fanboys. The behavior change is carried out continuously so that the behavior generated continues and becomes a habit. The behavior in question can be in the form of two things, namely verbal communication behavior and nonverbal communication behavior. This sustainable behavior occurs because the influence caused by K-pop girl groups is well received so this sustainable behavior continues to be applied in everyday life.